C9orf72-derived arginine-rich poly-dipeptides impede phase modifiers - Hitoki Nanaura (Nature Communications, 2021)
Nuclear import receptors (NIRs) regulate self-association of RNA-binding proteins as phase modifiers, while C9orf72-derived arginine-rich polydipeptides lead to aberrant phase transitions. Here the authors show in molecular basis how arginine-rich poly-dipeptides impede the ability of NIRs, particularly Kapβ2.